2019
DOI: 10.1111/ijfs.14166
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on quality characteristics of pickled and fermented sturgeon (Acipenser sinensis) meat in retort cooking

Abstract: Sturgeon (Acipenser sinensis) meat has not been fully utilised due to quality defects which were raised by Chinese sturgeon processing industry. This study was aimed to develop a high-quality sturgeon meat product and the effect of fermentation on qualities was studied. Results showed that fermentation with Saccharomyces cerevisiae could enhance 'mushroom', 'fruity' and 'chocolate' flavour by 1-octen-3-ol, ethyl acetate and 3-methyl-butanal; and enrich flavour through mild lipid oxidation and hydrolysis. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
(47 reference statements)
1
2
0
Order By: Relevance
“…In addition, the lowering pH could not only decrease the water‐holding capacity of muscle proteins but also induce the formation of the protein matrix, leading to the firmness of texture (Riebroy et al, ). A similar result was reported by Zhu et al (), who found a firmer sturgeon ( Acipenser sinensis ) meat after fermentation due to the much lower pH. Springiness and cohesiveness were associated with the internal bonding in the gel network of muscle protein (Visessanguan, Benjakul, Riebroy, & Thepkasikul, ).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the lowering pH could not only decrease the water‐holding capacity of muscle proteins but also induce the formation of the protein matrix, leading to the firmness of texture (Riebroy et al, ). A similar result was reported by Zhu et al (), who found a firmer sturgeon ( Acipenser sinensis ) meat after fermentation due to the much lower pH. Springiness and cohesiveness were associated with the internal bonding in the gel network of muscle protein (Visessanguan, Benjakul, Riebroy, & Thepkasikul, ).…”
Section: Discussionsupporting
confidence: 82%
“…TCA-soluble peptide content was determined according to Zhu et al [ 48 ] with some modifications. The PGP and PGPHs were mixed with an equal amount of 20% ( w / v) TCA solution followed by vortex for 10 s and standing for 30 min, and then centrifuged at 10,000× g for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Phospholipids have a greater impact on flavor than triglycerides because they contain polyunsaturated fatty acid groups and are more miscible with aqueous solutions of Maillard reactants ( Farmer & Mottram, 1990 ). Therefore, sturgeon surimi is prone to lipid oxidation during processing and storage, which results in the generation of volatile flavor compounds that impart a fishy smell and seriously impacts on the quality of surimi products ( Zhu et al, 2019 ). It is necessary to develop a new type of surimi product in which the gelatinous quality of unrinsed surimi is increased by the addition of selected substances and the fishy smell caused by lipid oxidation is alleviated.…”
Section: Introductionmentioning
confidence: 99%